Incommensurability and Related Matters
XXXIV, 338 p.
Keywords: Incommensurability and Related Matters draws together some of the most distinguished contributors to the critical literature on the problem of the incommensurability of scientific theories. It addresses all the various problems raised by the problem of incommensurability, such as meaning change, reference of theoretical terms, scientific realism and anti-realism, rationality of theory choice, cognitive aspects of conceptual change, as well as exploring the broader implications of incommensurability for cultural difference. While it offers new work, and new directions of discussion, on the topic of incommensurability, the book also recapitulates the history of the discussion of the topic that has taken place within the literature on incommensurability.